2015
DOI: 10.1139/juvs-2015-0021
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife research and management methods in the 21st century: Where do unmanned aircraft fit in?

Abstract: Since the turn of the century, emerging unmanned aircraft systems (UAS) have found increasingly diverse applications in wildlife science as convenient, very highresolution remote sensing devices. Achieved or conceptualized applications include optical surveying and observation of animals, autonomous wildlife telemetry tracking, and habitat research and monitoring. As the technology continues to progress and interest from the wildlife science community grows, there may yet be much untapped potential for UAS to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
183
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 210 publications
(207 citation statements)
references
References 110 publications
1
183
0
6
Order By: Relevance
“…Several studies have indicated that aerial image counts can be more accurate and consistent than live-observer counts (Boyd 2000, Frederick et al 2003, Buckland et al 2012, but a major drawback of the former is the significant time and effort required to manually analyze large volumes of imagery (Woodworth et al 1997, Béchet et al 2004. With burgeoning use of small low-flying unmanned aircraft, or drones, as a means of collecting very high-resolution aerial imagery of birds (Chabot and Bird 2015), as well as increasing possibilities to census birds in satellite imagery (LaRue et al 2017), the challenge of analyzing large volumes of imagery to detect and count subjects has been receiving increased attention.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that aerial image counts can be more accurate and consistent than live-observer counts (Boyd 2000, Frederick et al 2003, Buckland et al 2012, but a major drawback of the former is the significant time and effort required to manually analyze large volumes of imagery (Woodworth et al 1997, Béchet et al 2004. With burgeoning use of small low-flying unmanned aircraft, or drones, as a means of collecting very high-resolution aerial imagery of birds (Chabot and Bird 2015), as well as increasing possibilities to census birds in satellite imagery (LaRue et al 2017), the challenge of analyzing large volumes of imagery to detect and count subjects has been receiving increased attention.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, such operation is heavily restricted in most developed countries (Chabot and Bird 2015). Increasing the number of crews operating UASs within line of sight to achieve a complete census would eliminate problems with bias and coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Animals that have been monitored with UASs include surface-oriented marine, terrestrial, and tree-dwelling mammals, as well as waterbirds and aquatic reptiles (Chabot and Bird 2015). Compared to wildlife, the peer-reviewed literature on the use of UASs to count fish is scant, and the counts were made within relatively small study areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in using unmanned aerial vehicles (UAV) to study wildlife (see review by Chabot and Bird (2015)) offer promise and may improve data collection efficiency, especially in forested environments (Koh and Wich 2012). Small UAVs, such as multirotor platforms, are suitable for this task because they are easy to deploy, can fly over terrain that is difficult to access on foot, and can be programmed to follow specific trajectories.…”
Section: Introductionmentioning
confidence: 99%